Comparison of non-linear models for describing growth curves according to sex in Ovine Chiapas breed - Parés-Casanova, Pere Miquel (2015)
The aim of this study was to establish the growth curves in ovine Chiapas breed according to sex. Three models were used: logistic, von Bertalanffy and Gompertz. Body weight data were obtained from 66 males and 79 females of various ages. The three models showed similar goodness values; however, the logistic model was the best to describe the growth kinetics in this breed for both males and females, although this model tends to overestimate the initial body weights.